Distribusi Bantuan Kemanusiaan Korban Terdampak Banjir di Kota Parepare - Mulyana Machmud; Riza Amalia Rifani; Suwandi Suwandi (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
The community services activity carried out by the team of Andi Sapada Institute of Social and Business Parepare in the form of collecting donations and distributing aid to flood victims in Parepare City. The distribution of assistance was carried out in flood-prone areas by taking nine location points. The location points are Lompoe, Watang Bacukiki, Lapadde, Bumi Harapan, Lumpue, Galung Maloang, Kampung Baru, Tiro Sompe, and Ujung Baru sub-districts. This location was chosen based on the conditions and characteristics of flood-prone areas which refer to differences in flood intensity, number and population density. The conclusions obtained after this activity took place was that the flood disaster that occurred at several points in Parepare City at the end of 2022 resulted in material losses for individuals and communities in Parepare City. From field investigations, communications from related officials in the vicinity and monitoring of media coverage, several points were found that had the most severe impacts on Parepare City, namely in Lontangnge, Mangimpuru, dan Abbanuangnge the three of which were in Wattang Bacukiki sub-district, Bacukiki district and in Tegal, Lapadde sub-district, Ujung district. For this reason, the team took the initiative to donate and distribute aid whose visit was carried out on November 26 2022 and a handover was carried out by representatives from the team of lecturers from the Business Faculty majoring in Accounting with representatives of residents affected by the floods. It is hoped that the assistance will benefit residents, especially women and children who are there.